Extending Cognitive-Behavioural Theory and Therapy to Medically Unexplained Symptoms and Long-Term Physical Conditions: A Hybrid Transdiagnostic/Problem Specific Approach. Issue 4 (21st November 2016) - Salkovskis, Paul M.; Gregory, James D.; Sedgwick-Taylor, Alison; White, Julie; Opher, Simon; Ólafsdóttir, Sigrún
Abstract : Medically unexplained symptoms (MUS) are not only common and distressing, but are also typically poorly managed in general medical settings. Those suffering from these problems tend to incur significantly higher health costs than the general population. There are many effective treatments for different MUS; these are almost entirely based on cognitive-behavioural approaches. However, the wide range of treatment protocols tend to be 'syndrome specific'. As such, they do not generalise well in terms of training and application, making them expensive and difficult to disseminate, suggesting the desirability of developing a transdiagnostic approach. The general basis of such a CBT grounded transdiagnostic approach is considered, and the particular need to incorporate cognitive elements of both anxiety or health anxiety (threat) and depression (loss) is highlighted. Key empirically grounded and evidence-based processes (both specific and general) previously identified as underpinning the maintenance of MUS are delineated. The way in which these can be combined in a transdiagnostic model that accounts for most MUS presentations is presented and linked to a formulation-driven transdiagnostic treatment strategy, which is described. However, the need to take more syndrome-specific issues into account in treatment is identified, suggesting that the optimum treatment may be a hybrid transdiagnostic/specific approach with formulation, shared understanding, belief change strategies, and behavioural experiments at its heart. The generalisation of such approaches to psychological problems occurring in the context of 'long-term conditions' is identified as a further important development that is now within reach.